Bark Beetle Population Dynamics in the Anthropocene: Challenges and Solutions. (October 2019) - Biedermann, Peter H.W.; Müller, Jörg; Grégoire, Jean-Claude; Gruppe, Axel; Hagge, Jonas; Hammerbacher, Almuth; Hofstetter, Richard W.; Kandasamy, Dineshkumar; Kolarik, Miroslav; Kostovcik, Martin; Krokene, Paal; Sallé, Aurélien; et al.
Abstract : Tree-killing bark beetles are the most economically important insects in conifer forests worldwide. However, despite >200 years of research, the drivers of population eruptions and crashes are still not fully understood and the existing knowledge is thus insufficient to face the challenges posed by the Anthropocene. We critically analyze potential biotic and abiotic drivers of population dynamics of an exemplary species, the European spruce bark beetle (ESBB) ( Ips typographus ) and present a multivariate approach that integrates the many drivers governing this bark beetle system. We call for hypothesis-driven, large-scale collaborative research efforts to improve our understanding of the population dynamics of this and other bark beetle pests. Our approach can serve as a blueprint for tackling other eruptive forest insects. Highlights: Bark beetles are currently causing unprecedented damage to European and North American forests. Their population dynamics rarely have been studied in a hypothesis-driven manner incorporating exogenous biotic variables. We propose a conceptual framework to reveal the drivers of bark beetle populations. This approach can be equally applied to other eruptive insect pests.